Projeto mecânico de uma estação base de baixo custo para rastreamento de satélites - Costa, Bruno Henrique Correa da (Universidade Federal de São Carlos, 2021)
Advances in the telecommunications area through the use of satellites, an artificial equipment that orbit the planet, led to the emergence of technological innovations that allowed greater connectivity between people and equipment. The development of telecommunications satellites and the associated infrastructure requires high technical and financial resources. In this scenario, the present work aims to develop a mechanical design of a low cost base station for tracking, focusing on the rotor and its electromechanical components. For that, first the technical specifications and the literary search on existing solutions were raised for later elaboration of the conceptual project. Thus, the selection of components, such as stepper motors, control drivers, shafts, gears and bearings, was carried out, as well as the conception of their technical drawings for manufacturing. Thus, at the end of the work, the necessary details were delivered to assist in the future construction of a prototype, in order to carry out movement and control tests and evaluate the possibility of configuring the positioning angles, to receive telemetry from some selected satellite in orbit, configuring itself as a viable and low-cost solution for a tracking station, resulting in quality Brazilian technology and technological development in the Brazilian aerospace sector.
Mechanical design of a low cost base station for satellite tracking
Keywords: Projeto mecânico; Estação base de rastreamento de satélites; Mechanical design; Satellite tracking base station; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS